Improving Sharia Financial Inclusion through Advancements in Technology and Compliance with Sharia Principles - Irham Zaki; Fanet Muhammad Hanifan Paham; M Bastomi Fahri Zusak (IQTISHADIA, 2023)
This study aims to analyze the role of technology implementation and Sharia compliance in Islamic financial institutions in improving financial inclusion in Indonesia. This study employs a case study method using descriptive and explanatory techniques to investigate the relationship between the utilization of technology and compliance with Sharia principles in Peer-to-Peer Lending applied by ALAMI Sharia for contributing to the promotion of financial inclusion in Indonesia. This study focuses on analyzing Peer-to-Peer Lending ALAMI Sharia as the primary subject, specifically in relation to its impact on financial inclusion. The results of this study are then presented in a descriptive narrative manner to describe the findings in the field. Based on the four financial inclusion criteria used in this study: product penetration, product availability, product use, and product quality, it is generally understood that the implementation of advanced technology at Sharia financial institutions plays a crucial role in improving financial inclusion by providing service efficiency both in cost and time. Similarly, implementing Islamic financial principles contributes to enhancing financial inclusion in Indonesia by creating appealing financial products that comply with Sharia principles. These products are believed to ensure the high quality of financial products. This study provides empirical evidence on the prospects and the function of technology-based Islamic financial institutions, which will be very valuable for stakeholders in both practical and academic fields.